Edukasi Guna Pencegahan Terjadinya Flat Foot pada Komunitas Balita di Kelurahan Madyopuro Kecamatan Kedungkandang Kota Malang - Berlian Satria Negara; Rakhmad Rosadi (Lembaga Pengembangan Kinerja Dosen, 2026)
Flat foot is a common foot condition in humans and can lead to health problems if not properly managed. Education on flat foot prevention is very important to increase awareness and knowledge within the toddler community regarding ways to prevent and manage flat foot conditions. This study aims to determine the effectiveness of educational interventions in improving awareness and knowledge of parents of toddlers regarding flat foot prevention in Madyopuro Village, Kedungkandang District, Malang City. The methods used included counseling and educational sessions on flat foot prevention, as well as evaluation of mothers’ and children’s knowledge and awareness before and after the educational intervention. The results showed that education was effective in increasing parents’ awareness and knowledge regarding flat foot prevention. Therefore, education on flat foot prevention can serve as one of the strategies to reduce the prevalence of flat foot among children in Madyopuro Village, Kedungkandang District, Malang City.